Antibacterial Activity Of Tangerine Powder (Citrus reticulata Blanco.) Against Caries-Causing Bacteria (Streptococcus mutans) - Framesti Frisma Sriarumtias; Aji Najihudin; Nopi Rantika; Rita Nengsih (Universitas Pakuan, 2020)
Dental caries is caused by Streptococcus mutans, which lives in the oral cavity and causes plaque on the teeth. Dental caries treatment involves restoration or filling of tooth tissue that has been perforated due to dental caries. The purpose of this study was analyze the effectivity of tangerine juice powder in preventing the emergence of dental caries caused by Streptococcus mutans. The experimental method was used in this study started by making a powder from tangerine jiuce using freeze drying method, followed by testing the antibacterial activity using the disc diffusion method. In addition, the minimum inhibitory concentration (MIC) was also sought by measuring the diameter of the clear zone. The results showed that tangerine powder has antibacterial activity, with a minimum inhibitory concentration of 10%. The highest activity of tangerine powder to inhibit the growth of Streptococcus mutans bacteria was observed at concentration of 25% with an inhibition zone diameter of 15.8 mm, and is classified as having moderate inhibitory power. According to the result of this study is that tangerine juice powder has a good antibacterial activity against Streptococcus mutans and can be developed into a pharmaceutical ingredients to prevent dental caries.